Medical Pluralism Predicts Non-ART Use among Parents in Need of ART: A Community Survey in KwaZulu-Natal, South Africa - Pantelic, M.; Cluver, L.; Boyes, Mark; Toska, E.; Kuo, C.; Moshabela, M. (Springer New York LLC, 2014)
Despite documented common use of traditional healers and efforts to scale up antiretroviral treatment (ART) in sub-Saharan Africa, evidence on whether medical pluralism predicts ART use is inconclusive and restricted to clinic settings. This study quantitatively assesses whether medical pluralism predicts ART use among parents in need of ART in South Africa. 2,477 parents or primary caregivers of children were interviewed in HIV-endemic communities of KwaZulu-Natal. Analysis used multiple logistic regression on a subsample of 435 respondents in need of ART, who reported either medical pluralism (24.6 %) or exclusive public healthcare use (75.4 %). Of 435 parents needing ART, 60.7 % reported ART use. Medical pluralism emerged as a persistent negative predictor of ART utilization among those needing it (AOR [95 % CI] = .556 [.344 - .899], p = .017). Use of traditional healthcare services by those who need ART may act as a barrier to treatment access. Effective intersectoral collaboration at community level is urgently needed.